OFR-53-74 Research And Development Contract -Water Through The Drum, 120M Jeffrey Heliminer - Final Report On Contract H0232060, Respirable Dust Control On A Jeffrey 120M HELIMINER By Water Piped Through The Head - I. Introduction - Steven C. Goddard (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Since the passage of the Federal Coal Mine Health and Safety Act of 1969, the need for improved duet control methods has become imperative. It has been proposed that one promising dust control technique would be the application of water through the cutter drum. In November of 1972, the Jeffrey Mining Machinery Co., who had been pursuing the development of wet drum miners since 1969, completed the manufacture of a 120M HELIMINER which had sprays in front of the cutting bits on a fixed width drum. On June 27, 1973 Jeffrey and the Bureau of Mines signed the contract numbered B0232060 for the purpose of evaluating "the effectiveness of respirable dust control on a Jeffrey 120M HELIMINER by use of water piped through the head." This evaluation, as described by the contract, was to be accomplished by the collection and analysis of dust samples at various locations of an operating mine production section.